Magnetoliposomes based on magnetic/plasmonic nanoparticles loaded with tricyclic lactones for combined cancer therapy - Rio, Irina S.R. (2018)
Liposome-like nanoarchitectures containing manganese ferrite nanoparticles covered or decorated with gold were developed for application in dual cancer therapy, combining chemotherapy and photothermia. The magnetic/plasmonic nanoparticles were characterized using XRD, UV/Visible absorption, HR-TEM, and SQUID, exhibiting superparamagnetic behavior at room temperature. The average size of the gold-decorated nanoparticles was 26.7 nm for MnFe2 O4 with 5–7 nm gold nanospheres. The average size of the core/shell nanoparticles was 28.8 nm for the magnetic core and around 4 nm for the gold shell. Two new potential antitumor fluorescent drugs, tricyclic lactones derivatives of thienopyridine, were loaded in these nanosystems with very high encapsulation efficiencies (higher than 98%). Assays in human tumor cell lines demonstrate that the nanocarriers do not release the antitumor compounds in the absence of irradiation. Moreover, the nanosystems do not cause any effect on the growth of primary (non-tumor) cells (with or without irradiation). The drug-loaded systems containing the core/shell magnetic/plasmonic nanoparticles efficiently inhibit the growth of tumor cells when irradiated with red light, making them suitable for a triggered release promoted by irradiation.